2013
DOI: 10.1007/978-3-642-39212-2_15
|View full text |Cite
|
Sign up to set email alerts
|

From Security Protocols to Pushdown Automata

Abstract: Abstract. Formal methods have been very successful in analyzing security protocols for reachability properties such as secrecy or authentication. In contrast, there are very few results for equivalence-based properties, crucial for studying e.g. privacy-like properties such as anonymity or vote secrecy. We study the problem of checking equivalence of security protocols for an unbounded number of sessions. Since replication leads very quickly to undecidability (even in the simple case of secrecy), we focus on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Compared to [13], we no longer need to restrict the number of variables per transition (to one), we allow variables in key positions, and we are more flexible in the control-flow of the program (we may have arbitrary sequences of in and out actions).…”
Section: Decidability Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to [13], we no longer need to restrict the number of variables per transition (to one), we allow variables in key positions, and we are more flexible in the control-flow of the program (we may have arbitrary sequences of in and out actions).…”
Section: Decidability Resultsmentioning
confidence: 99%
“…To our knowledge, the only decidability result for an unbounded number of sessions is [13]. It is shown that trace equivalence can be reduced to the equality of languages of pushdown automata.…”
Section: Introductionmentioning
confidence: 99%
“…This class of processes is however insufficient for most anonymity properties. Finally, decidability results for an unbounded number of sessions were proposed in [CCD15b,CCD15a], but with severe restrictions on processes and equational theories.…”
Section: Related Workmentioning
confidence: 99%
“…[6], [9] for trace properties and [10], [11] for equivalence). However, protocols do use nonces in practice.…”
Section: Introductionmentioning
confidence: 99%